Monitoring Carbapenem-Resistant Enterobacterales in the Environment to Assess the Spread in the Community - Taro Urase; Saki Goto; Mio Sato (MDPI AG, 2022)
The usefulness of wastewater-based epidemiology (WBE) was proven during the COVID-19 pandemic, and the role of environmental monitoring of emerging infectious diseases has been recognized. In this study, the prevalence of carbapenem-resistant Enterobacterales (CRE) in Japanese environmental samples was measured in the context of applying WBE to CRE. A total of 247 carbapenem-resistant isolates were obtained from wastewater, treated wastewater, and river water. Treated wastewater was shown to be an efficient target for monitoring CRE. The results of the isolate analysis showed that WBE may be applicable to Escherichia coli-carrying New Delhi metallo-β-lactamase (NDM)-type carbapenemase, the Enterobacter cloacae complex and Klebsiella pneumoniae complex-carrying IMP-type carbapenemase. In addition, a certain number of CRE isolated in this study carried Guiana extended spectrum (GES)-type carbapenemase although their clinical importance was unclear. Only a few isolates of Klebsiella aerogenes were obtained from environmental samples in spite of their frequent detection in clinical isolates. Neither the KPC-type, the oxacillinase (OXA)-type nor the VIM-type of carbapenemase was detected in the CRE, which reflected a low regional prevalence. These results indicated the expectation and the limitation of applying WBE to CRE.